Tenacious of Their Liberties : the Congregationalists in Colonial Massachusetts. - Cooper, James F. (James Fenimore), 1955- (Religion in America., 1999)
Introduction. 1. The Implementation of the Congregational Way. 2. "A Mixed Form": Clerical Authority and Lay Liberty. 3. Lay "Rebellion" and Clerical Reaction: Antinomianism and Its Aftermath. 4. The Presbyterian Challenge. 5. Congregationalism in Crisis: The Halfway Covenant. 6. An Uneasy Balance. 7. Declension and Reform. 8. Clerical Conflict and the Decline of Sola Scriptura. 9. Perpetuation and Disintegration. 10. The Great Awakening and the Privatization of Piety.